An Analytical Study The Art of Figurative Language in Moana : An Analytical Study - Luh Wayan Ayanti; Ni Nyomen Deni Ariyaningsih (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This analysis explores the utilization and impact of various forms of figurative language in the script of the movie "Moana." The study delves into six types of figurative language: simile, metaphor, hyperbole, paradox, irony, and personification. The choice to focus on these six types is rooted in the writer's deep understanding of these specific forms, allowing for a more thorough and nuanced analysis. Through a meticulous examination of the script, it is revealed that personification and metaphor are the most prevalent, contributing significantly to the narrative depth and cultural richness of the film. The personification, in particular, enlivens it as a character and underscores its cultural significance in Polynesian lore. Additionally, metaphors and similes are instrumental in character descriptions and thematic elaboration, while hyperbole and irony inject humor and complexity into the storyline. Paradoxes are employed to provoke critical thinking about the story's underlying themes. Ultimately, this analysis underscores the indispensable role of figurative language in enriching the storytelling of "Moana" and enhancing its emotional resonance.